THE DEVELOPMENT OF ANALYTICAL METHOD OF ANTIOXIDANT ACTIVITY DETERMINATION USING DPPH (2,2-DIPHENYL-1- PICRYLHYDRAZYL) FREE RADICAL WITH MICROPLATE READER - Sari Handayani, Mitra
An analytical method in research laboratory has to be modified or developed in order to obtain the best analytical method. Determination of antioxidant activity against DPPH free radical was one of the most common assay used to observe biological activity of plants extract. The purpose of this research was to validate the analytical method antioxidant activity against DPPH free radical using microplate reader in order to fulfill the requirement of validation parameters that have been set for the method performance. Thus, the method can be applied for determinating antioxidant activity of a plants extract against DPPH free radical with some advantages like saving the time, cost, number of sample and reagent to be used, and more sample can be analyzed in a single measurement. Determination of antioxidant activity from vitamin C against DPPH free radical used microplate reader on Thermo Scientific Multiskan GO™instrument. Afterwards, the performance of this analytical method was tested for the validation parameters such as linearity, limit of detection, limit of quantitation, precision, and accuracy. Then, the validated method was used to determine the antioxidant activity (IC50) from methanol extract of Syzygium jambos, Eucalyptus deglupta, Psidium guajava, Syzygium samarangense, and Syzygium aromaticum against DPPH free radical. Based on the experiment, the values of correlation coeffisient of linearity parameter, limit of detection, limit of quantitation, recovery percent of acuracy parameter, and variance coefficient of intraday and interdays precision were 0.9990, 1.08 ?g/mL, 1.31 ?g/mL, 96.64-103.52%, 1.51% and 1.56%, respectively. Antioxidant activity (IC50) against DPPH free radical from vitamin C was 6.65 ?g/mL. IC50 values of methanol extract of Syzygium jambos, Eucalyptus deglupta, Psidium guajava, Syzygium samarengense, and Syzygium aromaticum were 10.83, 11.35, 20.74, 14.83, and 20.95 ?g/mL, respectively. Analytical method of determination antioxidant activity using DPPH free radical with microplate reader on Thermo Scientific Multiskan GO™instrument showed the valid result therefore it can be applied for determining of antioxidant activity from plants extract.